(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the linguocultural features of translating national realia in American short stories, focusing on the interaction between language, culture, and meaning in the translation process. National realia, as culture-specific elements, reflect unique aspects of a society’s history, traditions, values, and everyday life, and therefore present significant challenges for translators. The study analyzes various translation strategies used to render realia, including transliteration, descriptive translation, functional equivalence, and cultural substitution.